Discourses of 'class' in Britain in 'New Times'. Issue 2 (3rd April 2017) - Sutcliffe-Braithwaite, Florence
Abstract: In the 1980s, the New Times writers suggested that economic and cultural changes were ushering in an era where diverse identities were replacing 'class'. This was a vision which the Labour Party feared, but which Margaret Thatcher embraced. In her rhetoric, she celebrated what she saw as a decline in the significance of class identities and distinctions. This article examines the place and meanings of 'class' in subjective accounts of 'class' in the period, from 'ordinary' individuals. It argues that many people, when asked about 'class' in interviews or by Mass Observation, foregrounded 'ordinariness' as central to their identity. Many took 'seeing people as members of a class' to mean snobbishness or deference. 'Class' was frequently taken to mean pretentiousness and/or inferiority—and this was a highly negative meaning. Many asserted that they themselves had, or at least aspired to, a 'classless', socially egalitarian outlook, and were neither snobbish nor deferential. However, most people also identified and critiqued large, structural inequalities in British society. The place of 'class' in British society and culture in this period remained complex and often contradictory.